2020
DOI: 10.1021/acs.iecr.0c04233
|View full text |Cite
|
Sign up to set email alerts
|

Economic, Thermodynamic, and Environmental Analysis and Comparison of the Synthesis Process of Butyl Acetate

Abstract: The traditional production of butyl acetate (BA) has the problems of low equilibrium conversion rate and high energy consumption of product separation and purification. In this work, the production processes of BA by transesterification and esterification were simulated. Taking the annual total cost as the objective function, the process parameters of the two processes were optimized by the sequential iterative optimization method. The analysis showed that the total annual costs (TACs) of the two processes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Luo and Ierapetritou [109] examined numerous integrated LCA methods over a case study of two biomass-based p-xylene fabrication techniques and suggested essential insights appropriate to future LCA. Moreover, LCAs of the production of broadly employed titanium dioxide nanoparticles [110] and butyl acetate [111] furnished conceptual directing for more sustainable synthesis of both. This procedure was used in suggesting the conversion of agricultural land in groundwater-stressed areas from irrigated crop types to rain-fed crop types combined with diversification to solar harvesting, so-called "agrivoltaics" [112].…”
Section: Life-cycle and Systems Thinkingmentioning
confidence: 99%
“…Luo and Ierapetritou [109] examined numerous integrated LCA methods over a case study of two biomass-based p-xylene fabrication techniques and suggested essential insights appropriate to future LCA. Moreover, LCAs of the production of broadly employed titanium dioxide nanoparticles [110] and butyl acetate [111] furnished conceptual directing for more sustainable synthesis of both. This procedure was used in suggesting the conversion of agricultural land in groundwater-stressed areas from irrigated crop types to rain-fed crop types combined with diversification to solar harvesting, so-called "agrivoltaics" [112].…”
Section: Life-cycle and Systems Thinkingmentioning
confidence: 99%
“…In the current study, there are still weaknesses in PSD technologies, most notably a high energy consumption and low thermodynamic efficiency. A growing number of scholars have been interested in improving the thermodynamic efficiency of PSD process, and numerous studies have now found that remarkable energy savings can be achieved through the PSD process with heat integration. These findings indicate that the heat integration process has a higher thermal efficiency, less energy consumption, greater economic advantages, and environmental benefits than the conventional ones. However, this energy-saving and efficient technology makes the process complex and difficult to control.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional process included a CSTR followed by three distillation columns, while the intensified process included a reactive distillation column (RDC) followed by two distillation columns. Recently, Shen et al 9 optimized the butyl acetate production processes through simulations. They compared the transesterification and esterification reactions.…”
Section: Introductionmentioning
confidence: 99%
“…It is also used as an extracting agent in pharmaceuticals. Commonly used methods for the production of n -butyl acetate are the esterification of acetic acid with n -butanol and trans-esterification of methyl- or ethyl-acetate with n -butanol. Researchers have also studied the coproduction of ethyl acetate and butyl acetate. Among these, the most practiced method is liquid-phase esterification of acetic acid with n -butanol in the presence of an acid catalyst. This reaction is reversible and exothermic.…”
Section: Introductionmentioning
confidence: 99%